Spironolactone effect on cardiac structure and function of patients with heart failure and preserved ejection fraction: a pooled analysis of three randomized trials. (9th November 2022) - Ferreira, João Pedro; Cleland, John G.; Girerd, Nicolas; Bozec, Erwan; Rossignol, Patrick; Pellicori, Pierpaolo; Cosmi, Franco; Mariottoni, Beatrice; Solomon, Scott D.; Pitt, Bertram; Pfeffer, Marc A.; Shah, Amil M.; et al.
Abstract : Aims: Spironolactone is currently used in a large proportion of patients with heart failure and preserved ejection fraction (HFpEF), yet its effect on cardiac structure and function in a large population has not been well established. The aim of this study was to evaluate the impact of spironolactone on key echocardiographic parameters in HFpEF. Methods and results: An individual‐patient‐data meta‐analysis of three randomized trials (HOMAGE, Aldo‐DHF, and TOPCAT) was performed comparing spironolactone (9–12 month exposure) to placebo (or control) for the changes in left atrial volume index (LAVi), left ventricular mass index (LVMi), interventricular septum (IVS) thickness, E/e′ ratio, and left ventricular ejection fraction (LVEF) among patients with stage B (HOMAGE) or C (Aldo‐DHF and TOPCAT) HFpEF. Analysis of covariance was used to test the effect of spironolactone on echocardiographic changes. A total of 984 patients were included in this analysis: 452 (45.9%) from HOMAGE, 398 (40.4%) from Aldo‐DHF, and 134 (13.6%) from TOPCAT. The pooled‐cohort patient's median age was 71 (66–77) years and 39% were women. Median LAVi was 29 (24–35) ml/m 2, LVMi 100 (84–118) g/m 2, IVS thickness 12 (10–13) mm, E/e′ ratio 11 (9–13), and LVEF 64 (59–69)%. Spironolactone reduced LAVi by −1.1 (−2.0 to −0.1) ml/m 2 ( p = 0.03); LVMi by −3.6 (−6.4 to −0.8) g/m 2 ( p = 0.01); IVS thickness by −0.2 (−0.3 to −0.1) mm ( p = 0.01); E/e′ ratio by −1.3 (−2.4 to −0.2) ( p = 0.02); and increased LVEF by 1.7 (0.8–2.6)% ( p < 0.01). No treatment‐by‐study heterogeneity was found except for E/e′ ratio with a larger effect in Aldo‐DHF and TOPCAT (interaction p < 0.01). Conclusions: Spironolactone improved cardiac structure and function of patients with HFpEF.